Kurikulum Pembelajaran Bahasa Arab di Perguruan Tinggi - Noor, Fatwiah (ARABIYATUNA : Jurnal Bahasa Arab, 2018)
This paper present about the Arabic learning curriculum in universities in Indonesia. It discusses about curriculum concept in college from its history, that have changed from the past until now. Then, it discusses about Arabic learning viewed from learning concept and Arabic language it self. Then, the last point, the writer tried to discuss about Arabic learning curriculum in universities viewed from the aims and the learning process. This paper aims to give understanding and description about Arabic learning curriculum of universities by analyzing the curriculum that being used or facts about curriculum in universities. The writer finds that the Arabic learning curriculum in universities shows that Arabic learning depends on the learning it self in curriculum whether it as the aims of curriculum or as a tool to realize the aim of curriculum.